Post-discharge malaria chemoprevention in children admitted with severe anaemia in malaria-endemic settings in Africa: a systematic review and individual patient data meta-analysis of randomised controlled trials - Kamija S Phiri, ProfMD PhD; Carole Khairallah, MSc; Titus K Kwambai, MD PhD; Kalifa Bojang, MD PhD; Aggrey Dhabangi, MD PhD; Robert Opoka, MD PhD; Richard Idro, MD PhD; Kasia Stepniewska, PhD; Michael Boele van Hensbroek, ProfPhD; Chandy C John, ProfPhD; Bjarne Robberstad, ProfPhD; Brian Greenwood, ProfMD; et al. (Elsevier, 2024)
Summary: Background: Severe anaemia is associated with high in-hospital mortality among young children. In malaria-endemic areas, surviving children also have an increased risk of mortality or readmission after hospital discharge. We conducted a systematic review and individual patient data meta-analysis to determine the efficacy of monthly post-discharge malaria chemoprevention in children recovering from severe anaemia. Methods: This analysis was conducted according to PRISMA-IPD guidelines. We searched multiple databases on Aug 28, 2023, without date or language restrictions, for randomised controlled trials comparing monthly post-discharge malaria chemoprevention with placebo or standard of care among children (aged <15 years) admitted with severe anaemia in malaria-endemic Africa. Trials using daily or weekly malaria prophylaxis were not eligible. The investigators from all eligible trials shared pseudonymised datasets, which were standardised and merged for analysis. The primary outcome was all-cause mortality during the intervention period. Analyses were performed in the modified intention-to-treat population, including all randomly assigned participants who contributed to the endpoint. Fixed-effects two-stage meta-analysis of risk ratios (RRs) was used to generate pooled effect estimates for mortality. Recurrent time-to-event data (readmissions or clinic visits) were analysed using one-stage mixed-effects Prentice-Williams-Peterson total-time models to obtain hazard ratios (HRs). This study is registered with PROSPERO, CRD42022308791. Findings: Our search identified 91 articles, of which 78 were excluded by title and abstract, and a further ten did not meet eligibility criteria. Three double-blind, placebo-controlled trials, including 3663 children with severe anaemia, were included in the systematic review and meta-analysis; 3507 (95·7%) contributed to the modified intention-to-treat analysis. Participants received monthly sulfadoxine-pyrimethamine until the end of the malaria transmission season (mean 3·1 courses per child [range 1-6]; n=1085; The Gambia), monthly artemether-lumefantrine given at the end of weeks 4 and 8 post discharge (n=1373; Malawi), or monthly dihydroartemisinin-piperaquine given at the end of weeks 2, 6, and 10 post discharge (n=1049; Uganda and Kenya). During the intervention period, post-discharge malaria chemoprevention was associated with a 77% reduction in mortality (RR 0·23 [95% CI 0·08-0·70], p=0·0094, I2=0%) and a 55% reduction in all-cause readmissions (HR 0·45 [95% CI 0·36-0·56], p<0·0001) compared with placebo. The protective effect was restricted to the intervention period and was not sustained after the direct pharmacodynamic effect of the drugs had waned. The small number of trials limited our ability to assess heterogeneity, its sources, and publication bias. Interpretation: In malaria-endemic Africa, post-discharge malaria chemoprevention reduces mortality and readmissions in recently discharged children recovering from severe anaemia. Post-discharge malaria chemoprevention could be a valuable strategy for the management of this group at high risk. Future research should focus on methods of delivery, options to prolong the protection duration, other hospitalised groups at high risk, and interventions targeting non-malarial causes of post-discharge morbidity. Funding: The Research-Council of Norway and the Bill-&-Melinda-Gates-Foundation through the Worldwide-Antimalarial-Research-Network.